The 1918 influenza in Chiapas (Mexico). Actions and remedies to face an unknown illness - Lisbona Guillén, Miguel (2024)
As happened in other regions of the planet, the arrival of influenza in Chiapas (Mexico) showed the lack of knowledge of the viral origin of the disease that made it impossible to face the pandemic with the required capacity. In the case of Chiapas, we must add to this situation the political-military conflict that was experienced in its territory and the weakness of state public institutions to coordinate and address the health emergency. At this juncture, the isolationist actions carried out, and the remedies used and recommended, show the heterogeneity of explanations about the origin of the disease in a Chiapas with little presence of doctors. Through primary and secondary sources, the article describes, from historical methodology, some of the measures taken to stop the spread of influenza and that demonstrate the coexistence of medical interpretations to stop the progression of the disease and care for patients.